Roles of SME Financing in Inclusive Economic Growth and Poverty Reduction in Bangladesh - Banerjee, Prashanta K.; Rahman, Matiur (International Journal of Economics and Financial Issues, 2026)
The objective of this study is to examine the roles of SME, non-SME, and agricultural financing in inclusive economic growth and concomitant headcount poverty reduction in Bangladesh. ADF (Augmented Dickey-Fuller) and KPSS (Kwiatkowski-Phillips-Schmidt-Shin) tests for non-stationarity of time series variables, the ARDL (Autoregressive Distributed Lag) procedure for cointegration and the associated VECMs (Vector Error- Correction Models) are implemented for convergence toward long-term equilibrium, speed of adjustment toward it, long-run casual effects and short-run feedback effects. Annual data from 1976 through 2023 are employed. Data sources include the Bangladesh Bureau of Statistics and the Bangladesh Planning Commission. Evidences support financing of SMEs to positively influence inclusive real GDP (Gross Domestic Product) growth that in turn help poverty reduction. However, the reduction in poverty through inclusive economic growth alone is relatively subdued than direct SME financing. Agricultural financing has relatively more pronounced effects on poverty reduction. The converging speed of adjustment towards the long-run equilibrium, however, seems tepid. The short-run feedback effects appear reinforcingly positive. The policymakers in Bangladesh should stay focused on due financing to SMEs and agriculture for promoting inclusive economic growth and hence, mitigating poverty. To note, enhancing inclusive economic growth alone cannot sufficiently dent poverty. Other supportive measures and micro-business lending should as well be given a priority.